Nina Bouraoui’s Nos baisers sont des adieux: Ekphrasis and the Accumulation of Memories - Anna Rocca (Studies in 20th & 21st Century Literature, 2014)
This article aims to explore the function of the image and the purpose of the works of art in Franco-Algerian author Nina Bouraoui’s Nos baisers sont des adieux (2010). Similar to a scrapbook with short descriptions of people, places, and objects, the book itself does not contain any visual representations. In spite of this lack, the image—the latter intended as mental or physical picture that reproduces reality—is a central theme throughout the work. Because visual art is described and interpreted but not shown, I argue that, by means of ékphrasis, the word-image dialogue further enables the narrator to express the multiple aspects of her own subjectivity and the reader to participate in the emotional experience that visual art triggers. I also maintain that Bouraoui's decision to focus on the work of provocative, groundbreaking visual artists is a socio-political statement in and of itself.
Keywords: Ekprasis; Autobiography; Readership; Visual Art; Memory